Blood acetylcholinesterase and butyrylcholinesterase as biomarkers of cholinesterase depression among pesticide handlers. Issue 12 (4th September 2014) - Strelitz, Jean; Engel, Lawrence S; Keifer, Matthew C
Abstract : Objective: Agricultural pesticide handlers are at an elevated risk for overexposure to organophosphate (OP) pesticides, but symptoms can be difficult to recognise, making biomarkers invaluable for diagnosis. Occupational monitoring programmes for cholinesterase depression generally rely on measuring activity of either of the two common blood cholinesterases which serve as proxy measurements for nervous-system acetylcholinesterase activity: red blood cell acetylcholinesterase (AChE) and plasma butyrylcholinesterase (BChE). These biomarkers, however, may be affected differentially by some OPs and the relationship between them has not been well characterised. We aim to determine the association between blood AChE and BChE activity levels and assess whether they produce comparable classifications of clinical cholinesterase depression among OP pesticide handlers. Methods: Using blood samples from 215 participants of the Washington State Cholinesterase Monitoring Program, we quantified changes in AChE and BChE activity from before and after exposure to OP pesticides and calculated Pearson correlation statistics for correlation of AChE and BChE changes in activity, as well as weighted κ statistics for agreement of classification of clinical cholinesterase depression based on AChE versus BChE measurements. Results: AChE and BChE activity measurements are weakly negatively correlated in our study population. Reaching a clinical threshold for diagnosis of cholinesterase depression based on the AChE marker did not correlate with reaching clinical depression based on the BChE marker. Conclusions: Both AChE and BChE should be measured in monitoring programmes because they may both give potentially important but disparate classifications of clinical cholinesterase depression.